Vitamin D levels and depressive symptoms in patients with chronic heart failure. (15th March 2016) - Johansson, Peter; Alehagen, Urban; van der Wal, Martje H.L.; Svensson, Erland; Jaarsma, Tiny
Abstract: Background: Vitamin D (Vit D) is suggested to play a role in the regulation of physical function as well as in depression. Since, Vit D deficiency is common in patients with heart failure (HF), this study aims to explore if Vit D levels are associated with depressive symptoms and if this association is mediated by the patients' physical function. Method: 506 HF patients (mean age 71, 38% women) were investigated. Depressive symptoms and physical function were measured with the Centre for Epidemiological Studies Depression Scale and the physical function scale from the RAND-36. Vit D was measured in blood samples Results: At baseline there was no relationship between depressive symptoms and Vit D levels. However, at 18 months follow-up 29% of patients with Vit D < 50 nmol/l at baseline had depressive symptoms compared 19% of those with Vit D levels > 50 nmol/l (p < 0.05). Only in patients with Vit D < 50 nmol/l, Vit D correlated significantly to physical function and depressive symptoms (r = .29, p < 0.001 and r = .20, p < 0.01). In structural equation modelling an indirect association between Vit D and depressive symptoms was found, mediated by physical function (B = 0.20). This association was only found in patients with Vit D levels < 50 nmol/l. Conclusion: In HF patients with Vit D < 50 nmol/l, Vit D is associated to depressive symptoms during follow-up and this association is mediated by physical function. This relationship is not found in patients with Vitamin D level > 50 nmol/l.